Histopathological spectrum of gastrointestinal lesions in patientsundergoing gastrointestinal endoscopic biopsies- A Prospective study - Ritambhara Mishra; Shilpa Vahikar; Kanchan Shrivastava; Shaila Kumari Mitra; Vivek Mishra (Tropical Journal of Pathology and Microbiology, 2022)
Introduction: The disorders of gastrointestinal tract are responsible for a great deal of morbidityand mortality. Endoscopy in combination with biopsy plays an important role in the exact diagnosisof gastrointestinal tract disorders for further management. Objectives: The study was carried out todetermine the spectrum of histopathological lesions of GIT and to compare it with its endoscopicfindings. Methods: A prospective study was conducted on the GIT endoscopic biopsies and theirhistopathological assessment was done at the department of pathology, B.R.D. medical college fromJuly 2020 to June 2021. Endoscopies were performed using an endoscope. The biopsy specimensreceived were fixed in 10.0% formalin and routinely processed in H & E stain. Results: Out of 100endoscopic biopsies, the majority of cases were male predominance. In oesophagal biopsies, themost common non-neoplastic lesion was chronic non-specific esophagitis and SCC was the mostcommon malignancy in neoplastic lesions. Among stomach biopsies, the most common non-neoplastic lesion was chronic non-specific gastritis and malignancy was adenocarcinoma. Induodenal biopsies, 50% constituted non-neoplastic lesions and 50% had neoplastic pathology.Among colorectal biopsies, the most common non-neoplastic lesion was chronic non-specific colitisand the most common malignancy was adenocarcinoma. Conclusion: The incidence of the non-neoplastic lesion is higher than the neoplastic lesion. The most common non-neoplastic lesion ischronic non-specific gastritis and the most common malignancy is squamous cell carcinoma of theoesophagus. Among 100 cases, endoscopy reported 46% cases as neoplastic and 54% as non-neoplastic, whereas Histopathology revealed 35% as neoplastic and 65% as nonneoplastic.